Contraditório material, modelo cooperativo e democracia: a atuação das partes no funcionamento democrático do processo civil - Santos, Manuela Vidal e Silva Oliveira (2021)
The jurisdictional protection, in the face of the recognition of Constitution normative force before legal hermeneutics alteration, deals, today, with the right to a fair process, conducted by procedural fundamental rules, among which stands out the adversarial principle, understood, currently, as the right to influence and the prohibition of surprise decision. The material dimension of the contradictory requires a cooperative model of process, wich stimulates dialogue and participation, highlighting the procedural deliberative democracy. Given the criticism made to deliberation in the political space, the question is how does this affects the legal space and the democratic functioning of civil procedure.